Analisis Uji Neutrophil-Lymphocyte Ratio (NLR) Terhadap Pasien Kanker Kolorektal (KKR) Pasca-Operasi - Farida Noor Irfani; Magvira Ahmad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Colorectal cancer (CRC) is the third most common malignancy with the highest incidence and mortality worldwide. Currently, approximately 60-70% of CRC cases are diagnosed at an advanced stage. Early detection through screening strategies can provide better results in reducing the burden of disease. The Neutrophil-Lymphocyte Ratio (NLR) test plays a role in predicting the risk of tumor recurrence and the prognosis of CRC. Research related to the NLR test as a systemic inflammatory response in the early stages after surgery is still limited. This study aims to analyze the results of the NLR test in CRC patients who have undergone surgery. This study used a descriptive method with a cross-sectional approach. Data were obtained from the medical records of patients at Panti Rapih Hospital in Yogyakarta who met the inclusion criteria. Bivariate analysis was performed using the Statistical Package for the Social Sciences (SPSS) with the Chi-Square test to assess the influence of each risk factor (age, gender, and cancer stage) on the post-operative NLR ratio. The results showed that most CRC patients were male, with a mean age of 62.15 years, and most patients were in the elderly category (60-69 years), with most malignancies in stage II. Most patients had a normal postoperative NLR ratio (<5), indicating a low risk of recurrence. Age significantly affected the postoperative NLR ratio. The conclusion of this study is that an increase in postoperative NLR can assess the potential for recurrence and prognosis of CRC cases